RNAseq Reveals Sensitive, Concentration-Dependent Transcriptional Markers of Copper in Mytilus californianus Larvae and Adults - Hall, Megan R.; Moffett, James W.; Gracey, Andrew Y. (Frontiers in Marine Science, 2020)
Copper contamination of coastal waters is a long-standing problem in many regions. Copper water quality criteria in marine waters is often determined with bivalve embryo-larval toxicity tests which measure survival and normal development as endpoints. Gene expression data is increasingly incorporated into such assays as a complementary and sensitive marker of contaminant exposure or toxicity. Here we measured the impacts of copper on Mytilus californianus larval transcriptional profiles, and identified sensitive biomarkers of copper exposure. Key functional categories that were identified among these genes include biomineralization/shell formation, metal binding, and development. Finally, we compared the transcriptional response of larvae to that of adult gill tissue, and show in both datasets that patterns of declining transcript expression occur at lower copper concentrations than those required to induce increases in transcript expression, suggesting that down-regulated genes serve as the most sensitive marker of copper exposure.